Penggunaan Metode Sempoa dalam Meningkatkan Mental Aritmatika untuk Mengatasi Fobia Matematika Siswa SD - Afrilia Feronika; Aulia Putri; Adrias Adrias; Salmaini Safitri Syam (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2025)
Math phobia is a psychological disorder characterized by excessive fear of mathematical concepts or activities, which hinders students' learning process. This study aims to explore the use of the abacus method as an intervention in improving mental arithmetic and reducing math phobia in elementary school students. The abacus method, which has been proven effective in improving concentration and mental arithmetic skills, is integrated into learning to provide an interactive and fun learning experience. This study used a descriptive qualitative method involving 15 students and the third grade teacher of SDN 19 Tarung-Tarung, and used data collection techniques in the form of observation, interviews, and documentation. Data analysis used the Miles & Huberman research model. The results showed a significant increase in mental arithmetic skills and a decrease in students' anxiety levels in math subjects, which had a positive impact on students' learning motivation. The application of the abacus method can be an alternative strategy in designing more effective mathematics learning interventions to overcome math phobia.